Liability for defective products: a comparison between Part V and Part X of the Consumer Protection Act 1999 - Amin, Naemah (Ministry of Domestic Trade, Co-operatives and Consumerism, 2011)
From decomposed snail in the bottle of ginger bear (Donoghue v Stevenson) to a recent melamine crisis, the problem of defective goods continues to haunt consumers despite the existence of law dealing with liability for products. In fact product liability or liability for defective products which concerns with civil liability of those involved in the production and distribution of defective products may be considered as one of the most established areas of consumer protection. It provides a wide range of available grounds for consumers to pursue claims for injury caused by a defect in the product. Following the legal development in more developed countries, Part X of the Consumer Protection Act 1999 (the CPA) has adopted the regime of strict product liability. At the same time the CPA has improved the law on supply of goods. Part V of the Act introduced a new concept of implied guarantees, especially a guarantee as to acceptable quality which is very relevant to product liability. The question then arises as to whether there is any significant difference between Part V and Part X in relation to liability for defective products. This article aims to compare the protection afforded to consumers of defective products under the two regimes; contractual liability and strict product liability. The article particularly highlights the overlaps between the liability for quality standard and the liability based on defectiveness in product liability law.